Pengembangan sistem Informasi Profil dan Kegiatan Desa Pakis Kabupaten Magelang Berbasis Web - RISNA WULANSARI; Budi Hartono s,kom M,kom; TONI WIJANARKO ADI S,kom M,kom TONI WIJANARKO ADI (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The rapid development of information technology demands that village governments be able to provide fast, accurate, and transparent information services to the community. In Pakis Village, Magelang Regency, information delivery is still mostly carried out manually, such as through bulletin boards and verbal announcements. This method causes information to be distributed unevenly and less effectively. Therefore, a technology-based system is needed to improve the quality of village information services. This study aims to design and build a web-based information application for the profile and activities of Pakis Village, Magelang Regency, which can facilitate the management and dissemination of information to the community. The research method used is Research and Development (R&D) with the Waterfall system development model, covering the stages of requirement analysis, design, implementation, testing, and system maintenance. Data collection is conducted through observation, interviews, and documentation. This application is developed using HTML, CSS, JavaScript, and PHP programming languages, with MySQL as the database. The main features include village profile management, activity management, documentation gallery, village news, and an admin panel to manage data easily. The results show that the application helps village officials process information more effectively and efficiently, while allowing the public to access village information online anytime and anywhere. This application is expected to increase transparency, improve public service quality, and encourage community participation in village development.